Ownership Reform, State Ownership, Corporate Governance, and Agency Costs: The Case of Chinese Listed Companies - Vijayakumaran, R. (Research in World Economy, 2019)
The aim of this paper is to examine the effect of 2005-ownership reform and state ownership on the linkages between corporate governance mechanisms and agency costs for Chinese listed firms. Based on a large panel of Chinese listed firms, we find that following the reform managerial ownership, institutional shareholdings and debt financing have emerged as effective governance mechanisms to reduce agency costs only for private-controlled firms in the post reform period. Therefore, our study concludes that the effectiveness of corporate governance mechanisms differ between state and private controlled firms and state ownership still hinders effectiveness of governance mechanisms among Chinese listed firms. This study contributes to the literature on the implications of ownership reform and state ownership for corporate governance and agency costs at the firm level in transition economies.
Keywords: managerial ownership; debt financing